2014
DOI: 10.1155/2014/987927
|View full text |Cite
|
Sign up to set email alerts
|

Jussara (Euterpe edulisMart.) Supplementation during Pregnancy and Lactation Modulates the Gene and Protein Expression of Inflammation Biomarkers Induced bytrans-Fatty Acids in the Colon of Offspring

Abstract: Maternal intake of trans-fatty acids (TFAs) in the perinatal period triggers a proinflammatory state in offspring. Anthocyanins contained in fruit are promising modulators of inflammation. This study investigated the effect of Jussara supplementation in the maternal diet on the proinflammatory state of the colon in offspring exposed to perinatal TFAs. On the first day of pregnancy rats were divided into four groups: control diet (C), control diet with 0.5% Jussara supplementation (CJ), diet enriched with hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Previous data by our research group using a metabolic programming model revealed that supplementing the diet of pregnant rats with juçara berries (262.4 mg ACN/100 g fresh matter) reduced metabolic and inflammatory markers and increased Lactobacillus and Bifidobacterium spp. expression of genomic DNA and ZO‐1 gene in their offspring, demonstrating that phenolic compounds present in this fruit contribute to the control of inflammation and prevention of the development of chronic diseases through the intestinal pathway up until adulthood .…”
Section: Anthocyanins and Gut Microbiota Modulationmentioning
confidence: 99%
“…Previous data by our research group using a metabolic programming model revealed that supplementing the diet of pregnant rats with juçara berries (262.4 mg ACN/100 g fresh matter) reduced metabolic and inflammatory markers and increased Lactobacillus and Bifidobacterium spp. expression of genomic DNA and ZO‐1 gene in their offspring, demonstrating that phenolic compounds present in this fruit contribute to the control of inflammation and prevention of the development of chronic diseases through the intestinal pathway up until adulthood .…”
Section: Anthocyanins and Gut Microbiota Modulationmentioning
confidence: 99%
“…Studies in our group showed that jussara, besides the colorant power provided by the anthocyanins, is accounted for in several beneficial results from a perspective of health and well-being [27,[30][31][32]. Jussara pulp has been recognized as a superfood due to its composition, mainly, for the high concentration of anthocyanins and other phenolic compounds; in fact, these bioactive compounds are considered an attractive source of pigments and also means to ward off several diseases [27,33,34]. In this context, the pulp as a whole can be used in food preparations to confer color and beneficial biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, juçara exerted a beneficial effect in the offspring of mothers who consumed the fruit in the perinatal period. There was an improvement in the lipid profile, glucose concentration, body composition, and intestinal microbiota and a reduction in low-grade inflammation in the colon of 21-day-old puppies [ 20 ]. In contrast, supplementation with 2 % juçara of the diet of ApoE − / − mice for 12 weeks did not affect hepatic oxidation or the inflammatory profile of these animals [ 21 ].…”
Section: Introductionmentioning
confidence: 99%